The Covid-19 Pandemic, Policy Responses and Stock Markets in the G20 - Guglielmo Maria Caporale; Woo-Young Kang; Fabio Spagnolo; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper analyses the impact of the Covid-19 pandemic on stock market returns and their volatility in the case of the G20 countries. In contrast to the existing empirical literature, which typically focuses only on either Covid-19 deaths or lockdown policies, our analysis is based on a comprehensive dynamic panel model accounting for the effects of both the epidemiological situation and restrictive measures as well as of fiscal and monetary responses; moreover, instead of Covid-19 deaths it uses a far more sophisticated Covid-19 index based on a Balanced Worth (BW) methodology, and it also takes into account heterogeneity by providing additional estimates for the G7 and the remaining countries (non-G7) separately. We find that the stock markets of the G7 are affected negatively by government restrictions more than the Covid-19 pandemic itself. By contrast, in the non-G7 countries both variables have a negative impact. Further, lockdowns during periods with particularly severe Covid-19 conditions decrease returns in the non-G7 countries whilst increase volatility in the G7 ones. Fiscal and monetary policy (the latter measured by the shadow short rate) have positive and negative effects, respectively, on the stock markets of the G7 countries but not of non-G7 ones. In brief, our evidence suggests that restrictions and other policy measures play a more important role in the G7 countries whilst the Covid-19 pandemic itself is a key determinant in the case the non-G7 stock markets.
Keywords: C33; G15; E52; E62; 330; Covid-19 pandemic; stringency index; Covid-19 index; fiscal policy; shadow rates; stock markets